2020
DOI: 10.1192/bjp.2020.234
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of dopaminergic imaging as a biomarker for mild cognitive impairment with Lewy bodies

Abstract: Background Dopaminergic imaging is an established biomarker for dementia with Lewy bodies, but its diagnostic accuracy at the mild cognitive impairment (MCI) stage remains uncertain. Aims To provide robust prospective evidence of the diagnostic accuracy of dopaminergic imaging at the MCI stage to either support or refute its inclusion as a biomarker for the diagnosis of MCI with Lewy bodies. Method We conducted a prospective diagnostic accuracy study of baseline dopamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 36 publications
1
55
0
Order By: Relevance
“…We read with interest Roberts et al's paper on dopaminergic imaging as a biomarker for mild cognitive impairment with Lewy bodies (MCI-LB). 1 However, we believe that the authors’ conclusion that dopamine imaging is useful when Lewy body disease is suspected in a patient with MCI is not supported by the data presented. This otherwise well-designed and conducted study has issues that we commonly see in our Cochrane Dementia reviews of dementia tests.…”
mentioning
confidence: 71%
“…We read with interest Roberts et al's paper on dopaminergic imaging as a biomarker for mild cognitive impairment with Lewy bodies (MCI-LB). 1 However, we believe that the authors’ conclusion that dopamine imaging is useful when Lewy body disease is suspected in a patient with MCI is not supported by the data presented. This otherwise well-designed and conducted study has issues that we commonly see in our Cochrane Dementia reviews of dementia tests.…”
mentioning
confidence: 71%
“…As detailed previously (Donaghy et al, 2020;Roberts et al, 2021a;2021b), medically stable patients aged 60 years or older with a clinical diagnosis of MCI were recruited from local memory services in the North-East of England between April 2016 and September 2019. Potential study participants either reported the presence of any core clinical feature of DLB (complex visual hallucinations, rapid eye movement (REM) sleep behavior disorder, cognitive fluctuations, or parkinsonism not preceding cognitive impairment by more than 12 months), or any supportive clinical feature found in DLB, but not specific to this (e.g.…”
Section: Participantsmentioning
confidence: 99%
“…Following consent participants underwent a research-level assessment involving a semistructured interview, clinical and neurocognitive assessment and neurological examination by a medical doctor (RD ans SL), and imaging with FP-CIT, MIBG, and MRI (Firbank et al, 2021;Roberts et al, 2021a;2021b) at baseline, and then had longitudinal review at approximately annual follow-ups. Mean (SD) of maximum follow-up were 1.4 (0.98) years, with a maximum of 3.7 years from baseline.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations